Metallo‐Hydrogel‐Assisted Synthesis and Direct Writing of Transition Metal Dichalcogenides. (9th May 2019) - Zang, Xining; Hohman, J. Nathan; Yao, Kaiyuan; Ci, Penghong; Yan, Aiming; Wei, Minsong; Hayasaka, Takeshi; Zettl, Alex; Schuck, P. James; Wu, Junqiao; Lin, Liwei
Abstract: Two dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted interest for their compelling nanoscale new properties and numerous potential applications including fast optoelectronic devices, ultrathin photovoltaics, and high‐performance catalysts. Large‐scale growth of uniform TMDC materials is essential for investigating their physics and for their integration into devices. However, the wafer scale deposition of TMDCs on arbitrary nonselective substrates is still beyond the current state‐of‐the‐art. In this article, a method to synthesize layered TMDCs (MoS2 and WS2 ) at the wafer‐scale by sulfurization of transition metal ions (Mo 5+ and W 6+ ) in a gelatin template (metallo‐hydrogel) is reported. This process is adaptable to versatile substrates, including amorphous silicon oxide, high‐temperature quartz, and silicon. Although the products are nominally few layer materials, direct band photoluminescent (≈1.8 eV), similar to single‐ or decoupled multilayer MoS2 is observed. Finally, the solution‐based deposition enables contact printing of TMDC channels to be useable for device applications including thin film transistors with printed silver contacts using the same process. Abstract : Transition metal ions (Mo and W) drive self‐organization of a metallo‐hydrogel (Mo‐gel and W‐gel) into a lamellar nanostructured soft material. Subsequent chalcogenization at moderate temperatures in a sulfur atmosphere (420 °C) yields large area transition metal dichalcogenides (TMDCs) (MoS2 and WS2 ) on versatile substrates. Thin film transition is directly printed using metallo‐hydrogel converted TMDC as channel material.